THE CONTRIBUTION OF REFORMED THEOLOGY TO HERMENEUTICS - Jan van Doleweerd (Verbum Christi: Jurnal Teologi Reformed Injili, 2016)
Modern Hermeneutics is rooted in the realities of the readers and their culture. But what if readers are going to be their own Hermes? What kind of authority is left for the Bible as the Holy Word of God? The Calvinistic concept of autopistia, the self-convincing of Scripture, attempts to preserve the balance between tradition and inner light, between objectivity and subjectivity. It ties the Bible to God and the Holy Spirit but also to the readers and their context. With the autopistia as background this article contributes with a new hermeneutic frame with three vantage points: (1) the Text as Viva Vox Dei, (2) the reader, and (3) the historical and present hermeneutical community of readers, the church.